Cornelius Cardew behind the Iron Curtain - Żyła, Monika (Circuit, 2018)
The article considers the reception of Cornelius Cardew’s music at the Warsaw Autumn festival between 1960 and 1970. At that time, the state-backed festival—organized since 1956 in the capital of the People’s Republic of Poland—was considered to be an important and liberal showcase of European avant-garde from both sides of the Iron Curtain. In the article, I primarily look at the consequences of programming Cardew’s music at the festival held in a country belonging to the Eastern Block of Soviet Satellite States. I discuss further, how music critics and polish intellectuals interpreted Cardew’s music, especially his Treatise, and The Great Learning, and condemned it for their allegedly communist, pro-Chinese overtones, and explicit Maoist and Confucianist references. The rejection of Cardew’s music in Poland resulted from a bias towards his socialist, collective, and emancipatory tendencies expressed by his music. The article is based on my archival research conducted in the archive of the Polish Composers Union, the Warsaw Autumn archive, Paul Sacher Stiftung in Basel and Deutsches Polen - Institute in Darmstadt.